RESEARCH CAPACITY‐BUILDING IN AFRICA: NETWORKS, INSTITUTIONS AND LOCAL OWNERSHIP. (12th July 2012) - Marjanovic, Sonja; Hanlin, Rebecca; Diepeveen, Stephanie; Chataway, Joanna
Abstract: Networked models are often proposed as a means to enhance health research capacity‐building in Africa. This paper addresses a knowledge gap on what works and does not in capacity‐building in African research settings. It provides an analysis of how multi‐partner networks are built and how their success depends on building institutional level capacity‐strengthening within partner institutions. To do this, the paper focuses on the Wellcome Trust's African Institutions initiative, drawing on initial learning and evaluation project data. We identify priority areas for policy attention and share emerging early insights on mechanisms and strategies being implemented by consortia to address key challenges. Copyright © 2012 John Wiley & Sons, Ltd.